Anxiety Disorders and Nicotine Use among Undergraduate Students of Public Sector Medical University: A Cross-Sectional Study - Nighat, Ayesha; Ibrahim, Muhammad; Bibi, Aqsa; Haider, Ali; Saif, Shafna; Faisal Sultan, Muhammad Abdul Rab (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Anxiety disorders represent the most common mental health issue across many countries and multiple studies have shown that rates of smoking and nicotine practices are increased in individuals with anxiety disorders. Objectives: The objectives of our study are to evaluate the prevalence of nicotine use, the association between nicotine practices and anxiety levels as well as various anxiety disorders among medical students of Rawalpindi Medical University. Materials and Methods: A descriptive cross-sectional study involved 232 participants. Participants were selected through a non-probability convenient sampling technique and data was collected through a printed self-administered questionnaire and Hamilton, K10, DAAS scales. The responses were recorded, and data was analyzed. Results: Of the 232 participants, 43(29.1%) of males reported nicotine use, while no female was involved in nicotine practices. Nicotine consumption was not substantially correlated with age. Compared to non-users, who reported 2.1% and 28.6% anxiety, nicotine users reported higher levels of anxiety, with 65.5% reporting moderate anxiety and 9.3% reporting severe anxiety. Anxiety disorders like fears, insomnia, intellectual difficulties, and depression were significantly associated with nicotine use. Other anxiety disorders showed no significant association. Conclusion: The study identifies a significant association between nicotine practices and anxiety levels as well as various anxiety disorders.